Penerapan Restorative Justice dalam Penegakan Hukum di Kepolisian Resor Bima Kota - Muhammad Amrul Akbar; Gufran Gufran; Juhriati Juhriati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of restorative justice in law enforcement at the Bima City Police Resort and to identify the supporting and inhibiting factors in its execution. (Introduction) Restorative justice emerges as an alternative paradigm for resolving criminal cases that prioritizes the restoration of relationships among offenders, victims, and the community, and has gained a firm legal foundation through Police Regulation Number 8 of 2021. However, studies examining its implementation at the Regional Police Resort level in West Nusa Tenggara, particularly in Bima City, remain limited, despite the fact that the sociological characteristics of the local community may distinctively shape its acceptance and practice. (Methods) This research employs an empirical legal research method with a qualitative approach, adopting a socio-legal research type through in-depth interviews, participatory observation, and documentary study involving investigators, victims, offenders, and community leaders within the jurisdiction of the Bima City Police Resort. (Results) The findings reveal that the implementation of restorative justice has generally followed the established procedural framework, supported by the deliberative culture of the Bima community and the involvement of customary leaders, yet it continues to face challenges such as limited investigative personnel, low public legal literacy, divergent interpretations among law enforcement institutions, and insufficient legal certainty guarantees for victims. (Discussion) These findings affirm that the effectiveness of restorative justice is strongly shaped by local sociological context, underscoring the need for institutional capacity strengthening, cross-agency regulatory harmonization, and sustained public outreach to ensure that the principles of justice and legal certainty are proportionally realized at the Bima City Police Resort.